VARIASI CAMPURAN ALKALI AKTIVATOR PADA KUAT TEKAN BETON GEOPOLIMER DENGAN MENGGUNAKAN ABU CANGKANG TELUR BEBEK PADA PROSES PENGOVENAN - Kevin Erin Hasner; Sittati Musalamah; Prihantono Prihantono (Menara: Jurnal Teknik Sipil, 2019)
The objective of this research is to know the increase in the value of geopolymer concrete compressive strength using duck eggshell ash with a mixture of sodium silicate and sodium hydroxidein variations of 65%: 35%, 70%: 30%, and 75%: 25% at 7 days and 28 days with oven test specimensand control concrete which are only allowed to stand at room temperature. Ass Duck egg shells used are wastes which are burned with temperatures reaching 800 ° Cfor ± 4 hours using a ceramic burning oven. This study uses cylindrical test object with a diameter of10 cm and a height of 20 cm with the quality of the plan is fc '20 MPa. Testing of geopolymerconcrete compressive strength using a Crushing Test Machine tool. The geopolymer concretecompressive strength produced by heating concrete specimens at activator variations of 65%: 35%,70%: 30%, and 75%: 25% at 7 days ie 6,157 MPa, 12,314 MPa, and 3,736 MPa, and for 28 days ie2.547 MPa, 2.760 MPa, and 1.698 MPa. While the concrete specimens which were not heated thevalue of concrete compressive strength on activator variations were 65%: 35%, 70%: 30%, and 75%:25% at 7 days, ie 2.972 MPa, 3.991 MPa, and 1.486 MPa, and for 28 days, ie 1.401 MPa, 2.123MPa, and 1,273 MPa. It can be seen that the value of the maximum average compressive strength isin the variation of activator 70%: 30% with test specimens vented at a temperature of 79 ° C first.